Some Procedural Issues Concerning the Proceedings Before the Dispute Resolution Chamber of the Turkish Football Federatio - Alpaslan, Mehmet Emin (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
The Dispute Resolution Chamber occupies a central position among the four first-instance judicial bodies of the Turkish Football Federation and has jurisdiction over specific sports-related disputes. This article first examines the first-instance judicial bodies of the Turkish Football Federation, with particular emphasis on the Dispute Resolution Chamber. It then provides a detailed analysis of the Chamber's subject-matter and functional jurisdiction, followed by a systematic examination of the principal stages of the proceedings conducted before it. Particular attention is devoted to identifying the areas in which the Dispute Resolution Chamber enjoys exclusive jurisdiction and those in which it does not. The article also addresses selected technical and procedural issues that typically arise in proceedings before the Chamber. Furthermore, it examines the institutional structure of the Dispute Resolution Chamber, with particular emphasis on the impartiality and independence of its members, as well as the grounds for their recusal. Finally, the legal remedies available against decisions of the Dispute Resolution Chamber are analysed. The aim of this article is not only to provide a structured analysis of the institutional and procedural framework governing the Dispute Resolution Chamber, but also to identify practical challenges and contribute to a more in-depth academic discussion of these issues.